The availability levels of digital citizenship values in the new Palestinian curricula according to technology teachers in Gaza (Palestine Technical College Journal for Research and Studies, 2022)
The current research reveals the availability level of digital citizenship values in the new Palestinian curricula according to the technology teachers' of the governorate of Gaza and conceptualizes a suggested system to support and apply the digital citizenship's value in the new curricula. The researcher followed the descriptive methodology and chose a simple random sample consisting of (72) (female/male) teachers of technology from east and west directorate of Gaza at the Palestinian ministry of higher education in the governorate of Gaza. The researcher used a questionnaire consisting of 41 paragraph distributed on three fields; for identifying the availability level of digital citizenship values in the new Palestinian curriculum. The most important results of digital citizenship's value is related to protection which amounted to (59.44 %), followed by digital citizenship's value related to respect with a percentage of (58.70%), then finally digital citizenship's value related to education came with a percentage of (57.53%). It also revealed that there are statistical significant differences in the availability level of digital citizenship's value in the new Palestinian curricula attributed to years of employments' variable, in favor of the teachers employed from 5 to 10 years. In the light of the aforementioned results, the researcher conceptualized a suggested system to support and apply digital citizenship values in the new Palestinian curricula. the most important axis of which is building up a technological infrastructure suitable for supporting and applying digital citizenship starting with providing a matching set of computer labs sufficient for the number of students; developing university study plans; training teachers on employing technology and its tools safely through holding technological courses  under the supervision of the ministry.
Keywords: Digital citizenship values; new Palestinian curricula; the Palestinian ministry of education